BACK PAIN CHARACTERISTICS IN PHYSICAL AND OFFICE WORKERS - Swiat, Maciej; Kozłowska, Katarzyna; Pilis, Anna; Ptaszkowska, Lucyna; Pilis, Wieslaw; Stec, Krzysztof (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The aim of our study was to characterize back pain according to the occupation comprising physical and office work. Accordingly questionnaires from 100 physical workers (PW) and 100 office workers (OW) were collected. This dedicated questionnaire included 19 questions, of which 7 concerned demographic, work and stature features and 12 concerned back pain. Collected data showed that lower back pain was more common in PW but cervical pain in OW (p<0.001). Most common aetiology of back pain was spinal osteoarthritis, sciatica and scoliosis but of different spread in two groups (p<0.001). The history of back pain was most often above 5 years and there were significant differences in frequency, intensity and pain handling methods between groups (p<0.005). Back pain prophylaxis was well acknowledged in both groups (85% in OW, 91% in PW). Regular physical activity was considered the main prophylaxis method (67% in PW, 89% in OW) and similarly incorporated in both groups (p=0.691) however OW more often performed physical exercises (p<0.001). Physical therapy was used in both groups (PW 100%, OW 92%, p=0.004) but with variable efficacy according to responders. To conclude there were multiple differences between both groups in terms of the pain characteristic but with similar awareness and incorporated prophylaxis.